Study on Electrochemical Behavior of La(III) and Preparation of Al−La Intermetallic Compound Whiskers in Chloride Melt. Issue 2 (3rd November 2015) - Ji, De-Bin; Yan, Yong-De; Zhang, Mi-Lin; Wang, Pu; Yang, Xue; Jing, Xiao-Yan; Xue, Yun; Han, Wei; Hartmann, Thomas
Abstract : This paper exhibits a novel method to prepare the Al−La intermetallic compound whiskers on the liquid magnesium electrode at 1023 K. The electrochemical behavior of La (III) on a tungsten electrode in LiCl−KCl−MgCl2 −AlCl3 −LaCl3 melts was investigated by different electrochemical measurements. The result from chronopotentiometry shows that co-deposition of Mg(II), Li(I), Al(III) and La(III) ions occurs when the current intensity more than −190 mA. Quarternary Mg–Li–Al–La alloy was prepared by galvanostatic electrolysis, and the Al4 La intermetallic compound was identified via X-ray diffraction (XRD). The microstructure and micro−zone chemical analysis of Mg−Li−Al−La alloy were accomplished by scanning electron microscopy (SEM) with energy dispersive spectrometry (EDS). The results illustrate that lots of needle-like precipitates are synthesized on magnesium substrate. The crystal structure of needle-like precipitates was certified by transmission electron microscopy (TEM) with electron diffraction pattern. The result exhibits that the needle-like precipitates are Al−La intermetallic compound whiskers. The micro hardness of Mg−Li−Al−La alloy is remarkable improved with the help of Al−La intermetallic compound whiskers.